Answer:
gg
Step-by-step explanation:
Given the following functions below,
![\begin{gathered} f(x)=\frac{x+12}{x^2+4x-12}\text{ and} \\ g(x)=\frac{4x^2-16x+16}{4x+48} \end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%20f%28x%29%3D%5Cfrac%7Bx%2B12%7D%7Bx%5E2%2B4x-12%7D%5Ctext%7B%20and%7D%20%5C%5C%20g%28x%29%3D%5Cfrac%7B4x%5E2-16x%2B16%7D%7B4x%2B48%7D%20%5Cend%7Bgathered%7D)
Factorising the denominators of both functions,
Factorising the denominator of f(x),
![\begin{gathered} f(x)=\frac{x+12}{x^2+4x-12}=\frac{x+12}{x^2+6x-2x-12}=\frac{x+12}{x(x+6)-2(x+6)}=\frac{x+12}{(x-2)(x+6)} \\ f(x)=\frac{x+12}{(x-2)(x+6)} \end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%20f%28x%29%3D%5Cfrac%7Bx%2B12%7D%7Bx%5E2%2B4x-12%7D%3D%5Cfrac%7Bx%2B12%7D%7Bx%5E2%2B6x-2x-12%7D%3D%5Cfrac%7Bx%2B12%7D%7Bx%28x%2B6%29-2%28x%2B6%29%7D%3D%5Cfrac%7Bx%2B12%7D%7B%28x-2%29%28x%2B6%29%7D%20%5C%5C%20f%28x%29%3D%5Cfrac%7Bx%2B12%7D%7B%28x-2%29%28x%2B6%29%7D%20%5Cend%7Bgathered%7D)
Factorising the denominator of g(x),
![\begin{gathered} g(x)=\frac{4x^2-16x+16}{4x+48}=\frac{4(x^2-4x+4)}{4(x+12)} \\ \text{Cancel out 4 from both numerator and denominator} \\ g(x)=\frac{x^2-4x+4}{x+12}=\frac{x^2-2x-2x+4}{x+12}=\frac{x(x-2)-2(x-2)}{x+12}=\frac{(x-2)^2}{x+12} \\ g(x)=\frac{(x-2)^2}{x+12} \end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%20g%28x%29%3D%5Cfrac%7B4x%5E2-16x%2B16%7D%7B4x%2B48%7D%3D%5Cfrac%7B4%28x%5E2-4x%2B4%29%7D%7B4%28x%2B12%29%7D%20%5C%5C%20%5Ctext%7BCancel%20out%204%20from%20both%20numerator%20and%20denominator%7D%20%5C%5C%20g%28x%29%3D%5Cfrac%7Bx%5E2-4x%2B4%7D%7Bx%2B12%7D%3D%5Cfrac%7Bx%5E2-2x-2x%2B4%7D%7Bx%2B12%7D%3D%5Cfrac%7Bx%28x-2%29-2%28x-2%29%7D%7Bx%2B12%7D%3D%5Cfrac%7B%28x-2%29%5E2%7D%7Bx%2B12%7D%20%5C%5C%20g%28x%29%3D%5Cfrac%7B%28x-2%29%5E2%7D%7Bx%2B12%7D%20%5Cend%7Bgathered%7D)
Multiplying both functions,
C) x = -19/10 because when solving it with substitution u get x=-19/10 & y=153/10
Answer:m=p/x - n, n=p/x-m
Step-by-step explanation: I hope this is what you are looking for.